WHAT ARE THE DETERMINANTS OF COMMERCIAL BANK PERFORMANCE IN CHINA? DID THE SUB-PRIME CRISIS HAVE ANY IMPACT? - Yuan, Haiyan (2010)
The US sub-prime mortgage crisis now considered as the worst crisis and was expanded to global economy, causing volatility of financial market and credit contraction. In addition, China’s banking system improving efficiency and resources allocation through reform since 1978. It is reasonable to assume that the statue and competition capability of Chinese banks was enhanced in the worldwide trading businesses. Hence, this paper analyzes determinants of bank performance for China banking system using bank specific and macroeconomic factors over the period 2003-2009 as well as to capture the effects of the crisis in China banking system. Results show that capital strength, liquidity, non-interest income and bank size are important bank specific characteristics explaining bank performance during 2003 to 2009. Turning to macroeconomic conditions, the effect of inflation is also important determinant of banking performance. In addition, a comparing results of bank performance before and during the crisis show that liquidity is very important for bank profits, holding high level of liquid assets lead to higher profits in China. Finally, there is little evidence that China commercial banks suffer from great losses. By contrast, Chinese banks avoided a heavy damage the crisis and performed better during the crisis.